Analysis Of The Influence Of Financial Literacy, Risk Perceptions, And Lifestyle On Transaction Decisions Through Fintech Payment Paylater On Students In The City Of Semarang - Eva Purnamasari; Rifah Dwi Astuti; Sri Wahyuni; Sandi Supaya; Ana Putri Nastiti (International Journal of Economics, Business and Innovation Research, 2024)
Indonesia is one of the countries that has great potential for the growth of fintech transactions as evidenced by the various new products emerging and supported by the large number of internet users in Indonesia, where the younger generation occupies the highest portion of fintech users. One of the biggest contributors to growth is fintech payment paylaters found in e-commerce transactions. Students, as generation Z who were born and grew up surrounded by technology, are a generation that is very adaptive in adopting paylater products. However, the decision to pay using paylater requires adequate financial literacy, an understanding of the transaction risks, and what needs to be taken into account is the lifestyle of today's students which could potentially harm their collectability at SLIK OJK if not carefully considered and taken into account. This research uses a descriptive quantitative study that uses an online survey method via Google Form to students in the city of Semarang who have made transactions using PayLater. The results of this research show that there is an influence of Financial Literacy, Risk Perception and Lifestyle together on the decision to make transactions via fintech payment paylater among students in Semarang City. However, partially, only lifestyle variables influence the decision to make transactions using fintech payment paylater.